Perception and use of fat claims on food labels and consumer behaviour towards food products with fat claims: A Nottingham case study - Do, Thi Thanh Huong (2015)
Literature in consumer behaviour toward food and nutrition shows a lack of researches penetrating the perception and use of fat claims on the label of food products and consumer behaviour toward such product categories in the setting of real world. This study provides an insight into these issues based on questionnaires and observations in Nottingham city. The results indicate a genuine interest in the information of fat content on the package along with an overall good understanding of the healthiness of the products with such claims, though the understanding varies across product categories. The use of fat claims when shopping is relatively promising, and the degree of use is found to be compatible with the level of healthiness of product. Observed consumer behaviour does not stay in line with what is reported in questionnaires, revealing an over-reporting issue. In real setting, consumers prefer regular or full fat products to lighter versions. Socio-demographic factors are examined, figuring out a prevalence of women in the interest and use of fat claims. Other demographic factors do not seem to carry any causal effects. This study highlights the need for enhancing consumer understanding and use of health-related claims.